Significant Risk of Life Threatening Infections in Elderly Patients With Inflammatory Bowel Disease Receiving Anti-TNF Therapy - Ahmad Najib Bin Azmi; Way-Seah Lee; Ruey Terng Ng; Sik-Yong Ong; Sanjiv Mahadeva; Khean-Lee Goh; Ida Hilmi (Elsevier, 2024)
Non-Indexed Publication